CLINICAL AND SEROLOGICAL FEATURES IN AN 11-MONTH-OLD INFANT WITH PAROXYSMAL COLD HEMOGLOBINURIA - Radonjić, Zorica; Andrić, Biljana; Jovanović, Ankica; Mićić, Dragan; Dimić, Ana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Paroxysmal cold hemoglobinuria (PCH) is an uncommon form of autoimmune hemolytic anemia (AIHA). A specific etiological factor has not been determined yet. The pathogenesis of the disease is explained by the presence of “biphasic hemolysin” or low-affinity IgG autoantibody, which in most cases binds to the erythrocyte P antigen, binding components of complement until the complete activation of the cascade and hemolysis of erythrocytes. The disease typically presents in children following an acute infection, usually involving the upper respiratory tract or gastroenteritis. Case report: We present an 11-month-old female infant who was admitted to the Intensive Care Unit of the Institute due to vomiting, anemia, yellow discoloration of the skin and mucous membranes, dark-red-colored urine, and general weakness. Two days prior to admission, she had a nasal discharge. Initial blood tests revealed a hemoglobin level of 63 g/L, hematocrit at 17.3%, reticulocyte count of 1.76%, leukocytosis, thrombocytosis, elevated C-reactive protein at 75.7 mg/L, lactate dehydrogenase at 5365 IU/L, total/indirect bilirubin at 67.9/64.5 µmol/L, and decreased haptoglobin. No schizocytosis was evident in peripheral blood. Polyspecific direct antiglobulin test (DAT) was positive 3+ and monospecific DAT was C3d 1+. The infant was treated with intravenous immunoglobulins, a single unit of red blood cells transfusion, parenteral dual antimicrobial therapy, and a single dose of corticosteroids accompanied by intravenous hydration and correction of electrolyte disturbances. On the tenth day upon admission, blood samples were taken for the Donath-Landsteiner (DL) test, which showed the presence of “biphasic hemolysin” and confirmed the diagnosis of PCH. Conclusion: Clinical recognition of PCH, the transient nature of “biphasic hemolysin” and the possibility of performing the DL test depend on the timely confirmation diagnosis of this rare form of AIHA.